Influence of the vanadium(V) concentration on the structure of K2O—P2O5—WO3—V2O5 glasses - Terebilenko, K.V.; Zozulya, V.O.; Chornii, V.P.; Nedilko, S.G.; Slobodyanik, M.S. (Reports of the National Academy of Sciences of Ukraine, 2021)
The peculiarities of a glass formation for the K2O—P2O5—WO3—VмO5 system is determined by the K/V ratio and the content of WO3 and V2O5 oxides. The synthesis of glass has been carried out in a two-stage scheme, including the homogenization at 1000 °C and the annealing at 300 °C. According to the IR spectroscopy of the studied samples, the presence of phosphate, vanadate, and tungstate tetrahedra as network-forming fragments has been established. An increase in the content of WO66– in the obtained glass with the concentration of WO3 in the initial charge is shown. In the interval of V2O5 concentration from 2.8 to 32.5 %, transparent amorphous glasses with a color from yellow to light brown are obtained.